The Influence of Competence, Motivation, and Work Discipline on Employee Performance (Case Study of Bappelitbangda Lamongan Regency) - Andini Finna Febrianti; Muhamad Imam Syairozi; Abid Muhtarom (Sean Institute, 2024)
This study aims to determine the influence of Competence, Motivation and Work Discipline on Employee Performance both partially, simultaneously and the most dominant variables. The method of collecting data through a questionnaire, using the Likert scale. The results of the study show that Work Competence and Discipline partially have a positive and significant effect on employee performance. Meanwhile, motivation has a negative and insignificant effect on employee performance. Simultaneously, Competence, Motivation, and Work Discipline have a positive and significant effect on employee performance. The most dominant variable of work discipline.